Stratigraphy of the volcanic deposits in the high catchment of mayo river, department of Nariño - Naranjo-Henao, José Luis; Pulgarín-Alzate, Bernardo Alonso; Narváez-Marulanda, Blanca Liliana (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2010)
The drainage basin of Mayo river in the municipalities of San Pablo and La Cruz, Nariño State, is an example of a volcanic shaped filled valley. Doña Juana, Ánimas and Cerro Petacas are volcanoes that have been previously considered as Doña Juana volcanic complex. The geology of the zone is represented by several units of volcanic origin, which lie on the methasedimentary rocks of Quebradagrande Complex and some hypoabisal igneous bodies. The catchment of Mayo river has been filled with products of these volcanoes, and partially drained out, in several occasions. Volcanic behavior of the complex and specifically the Doña Juana volcano, represented by some deposits of the Mayo river, shows that it had been dominantly of explosive type with some sporadic effusive episodes. The main volumes are constituted by ash and pumice flow, ash and blocks and debris flow deposits, forming in some cases ignimbrites units. With the recollected data until now, an evolutive activity history of the volcanoes complex is proposed. Three eruptive epochs are outlined, which are characterized each of one for presenting many different volcanic deposits with an accumulated thickness of 350m.